2012
DOI: 10.1118/1.3700401
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic tomography and fluorescence molecular tomography: A comparative study based on indocyanine green

Abstract: Purpose: Both photoacoustic tomography (PAT) and fluorescence molecular tomography (FMT) can be used for molecular imaging when contrast agents are administrated. The goal of this work is to comparatively evaluate the performance of reflection-mode PAT and FMT in common phantom when indocyanine green (ICG) was used as a contrast agent. Methods: Reflection-mode PAT and FMT systems were developed. Target embedded in a background phantom with different ICG concentration, size, and depth location was examined. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 32 publications
(25 reference statements)
1
41
0
Order By: Relevance
“…10 ICG and ICG derivatives were utilized as rare molecular NIR PAI contrast agents even though there are other photophysical parameters – like the significant fluorescence of ICG derivatives, see below – that do not make them ideal PAI contrast agents. 11 Irrespective of the shortcomings, the utilization of ICG suggests its use as the benchmark dye.…”
Section: Introductionmentioning
confidence: 99%
“…10 ICG and ICG derivatives were utilized as rare molecular NIR PAI contrast agents even though there are other photophysical parameters – like the significant fluorescence of ICG derivatives, see below – that do not make them ideal PAI contrast agents. 11 Irrespective of the shortcomings, the utilization of ICG suggests its use as the benchmark dye.…”
Section: Introductionmentioning
confidence: 99%
“…This shows the potential for us to combine fluorescence molecular tomography (FMT) with photoacoustic tomography. While FMT has lower spatial resolution than PAT, it has higher specificity than photoacoustic imaging techniques and the combination of PAT and FMT would provide complementary information for breast cancer detection [26]. …”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, PAT has relatively low sensitivity compared to pure optical imaging due to the limitations of acoustic transducers. 23 Additionally, the presence of endogenous photoacoustic signals in some normal organs, such as the kidney, liver, spleen and heart, may interfere with specificity of PAT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…24 In contrast to conventional two-dimensional (2D) fluorescence molecular imaging, FMT provides improved localization and quantification in deep tissues. 2325 Previously, we reported that FMT was more sensitive and specific for the detection of low concentration contrast agents in tissues compared with PAT. 23 However, FMT has limited spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation